Analysis of the musculoskeletal pain risk profile through observation of work posture in minimarket employees - Laeto, Arwan Bin; Putri, Siti Sarahdeaz Fazzaura; Agustine, Vania; Hasbi, Alfian; Zulissetiana, Eka Febri (Surya Hijau Manfaat, 2025)
Musculoskeletal pain refers to the discomfort experienced in the musculoskeletal system as a result of various pain-inducing factors. Musculoskeletal pain is a leading cause of disability and absenteeism in the workplace. The primary causes of declining health among workers include occupational injuries (29.5%), overtime (25.9%), and ergonomic factors (13.7%), significantly influence occupational health and can adversely affect organ function. The study was conducted through observational approach with a cross-sectional design and primary data collected using the Nordic Body Map (NBM) questionnaire and the Rapid Entire Body Assessment (REBA). The study population is mini market employees and sample comprises were employees who fulfil inclusion and exclusion criteria as many as 50 respondents by using non-probability sampling technique. The results of study were obtained that the majority of workers belong to the age group of under 35 years, as many as 49 individuals (98%) and more than half of the respondents are predominantly female, accounting for 52% of the total. Furthermore, the study indicates that the dominant